DOI: 10.11606/d.17.2008.tde-07102008-173614
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização clínica-demográfica das internações psiquiátricas na região de Ribeirão Preto - SP entre 1998 e 2004

Abstract: At the beginning of the 1990s, psychiatric hospitalization costs were the secondlargest source of all hospitalization costs in Brazil. Since 1992, as a result of the Ministry of Heath guidelines, there have been changes in the characteristics of these hospitalizations. Psychiatric hospitals have progressively ceased to be a part of the core health care system, and there has been an increase in the outpatient service network. The 13th Regional Health Authority (DRS XIII), headquartered in Ribeirão Preto, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
19

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 79 publications
0
1
0
19
Order By: Relevance
“…At this unit, previous studies (10)(11) have already reported on the predominance of interned women, with percentages ranging from 51 to 56%. A research also performed at a psychiatric internment unit of a general hospital characterized the populati on hospitalized over a ten-year period, which comprised 47.1% of women (12) .…”
Section: Discussionmentioning
confidence: 70%
“…At this unit, previous studies (10)(11) have already reported on the predominance of interned women, with percentages ranging from 51 to 56%. A research also performed at a psychiatric internment unit of a general hospital characterized the populati on hospitalized over a ten-year period, which comprised 47.1% of women (12) .…”
Section: Discussionmentioning
confidence: 70%
“…Diante da importância da abordagem psicossocial na atenção à pessoa com sofrimento mental grave e persistente, admite-se que os CAPSs constituem o principal eixo da Política Nacional de Saúde Mental; mas a extensão da cobertura dos serviços de saúde mental ainda é limitada em muitos municípios, por ser insuficiente o número de equipamentos e de recursos humanos. Isso acaba por sobrecarregar os serviços já implantados, prejudicando a qualidade do vínculo estabelecido e do atendimento (Barros, 2008;Castro, 2009;Conselho Regional de Psicologia, 2009;Bezerra & Dimenstein, 2011).…”
Section: Discussão E Resultadosunclassified
“…Nessa vertente, pesquisas mostram que há relação direta entre suporte familiar ou relações familiares harmoniosas, estabilidade do quadro e menor número de internações (Barros, 2008;Silva, Stefanelli, 1991;Sgambati, 1983).…”
Section: O Papel Da Família No Cuidadounclassified